Renal hypouricemia complicated with kidney stone: a case report - Yang, Yuhao; Mu, Xingyu; Wu, Zengxiang; An, Zhenmei; Li, Shuangqing (Frontiers in Medicine, 2024)
Renal hypouricemia (RHUC) is a rare autosomal recessive disorder characterized by impaired renal tubular uric acid reabsorption and abnormally high uric acid clearance, which may be manifested by reduced serum uric acid (SUA) levels and elevated fractional excretion of uric acid (FE-UA >10%). Most RHUC patients are often asymptomatic or have accidentally decreased SUA levels during health examinations, while others develop kidney stones and exercise-induced acute kidney injury (EIAKI). We now report a case of RHUC complicated with an asymptomatic kidney stone, we identified a heterozygous mutation of c.269G>A (p.R90H) and a novel heterozygous mutation of c.674C>G (p.T225R) in the SLC22A12 gene in the patient through the whole exons gene detection (NGS method). This case offers valuable insights into the mechanisms, clinical management, and prognosis of RHUC and its associated complications.